2018
DOI: 10.18632/aging.101563
|View full text |Cite
|
Sign up to set email alerts
|

A new risk score based on twelve hepatocellular carcinoma-specific gene expression can predict the patients’ prognosis

Abstract: A large panel of molecular biomarkers have been identified to predict the prognosis of hepatocellular carcinoma (HCC), yet with limited clinical application due to difficult extrapolation. We here generated a genetic risk score system comprised of 12 HCC-specific genes to better predict the prognosis of HCC patients. Four genomics profiling datasets (GSE5851, GSE28691, GSE15765 and GSE14323) were searched to seek HCC-specific genes by comparisons between cancer samples and normal liver tissues and between diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 74 publications
1
21
0
Order By: Relevance
“…The rapid development of bioinformatics has produced numerous tools for the identification of biomarkers. 11 Weighted gene co-expression network analysis (WGCNA) is an effective tool that can be used to identify relevant patterns of the genes to determine relevant modules and key genes for specific diseases. 12 This algorithm has been extensively used to identify biomarkers at the transcriptional level.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of bioinformatics has produced numerous tools for the identification of biomarkers. 11 Weighted gene co-expression network analysis (WGCNA) is an effective tool that can be used to identify relevant patterns of the genes to determine relevant modules and key genes for specific diseases. 12 This algorithm has been extensively used to identify biomarkers at the transcriptional level.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified a molecular subtyping system of Asian HCC which could predict postoperative survival and recurrence. Unlike previous studies using only few genes 9,10 , our molecular signature was comprised of a large panel of 185 HCC-characteristic prognostic genes screened by a comprehensive analysis of the whole gene set profiles and follow-up information of each participant. This method made the identified molecular subtype more representative of the intrinsic heterogeneity of the cancer on the basis of its clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the multivariate Cox regression analysis results, we developed a prognostic risk score formula. The optimal prognostic mRNA expression levels were multiplied by the relative regression coefficients as follows [ 18 20 ]: …”
Section: Methodsmentioning
confidence: 99%